Perception of Mothers Regarding Malnutrition in Children Under Five Years Old in Muzaffargarh: Perception of Mothers Regarding Malnutrition in Children - Farooq, Zambeel; Masih , Sarfraz; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2022)
Malnutrition is still a serious issue that mostly affects children under the age of five worldwide, not just in impoverished nations. Early on in life, ensuring that children get the nutrients they need is critical to their immune system health, as well as their physical and intellectual growth Objectives: To explore the perception of mothers regarding malnutrition in children under five years old in Muzaffargarh. Methods: This was a descriptive qualitative study carried out in Muzaffargarh, Punjab. Overall 35 participants were employed in the study from Tehsil headquarters Jatoi, Muzaffargarh. The participants were interviewed and the data was audio recorded and in written notes. Thematic analysis was done once the data was collected. Results: The majority (48.6%) of the participants was from the age group of more than 35 years and 71.4% of the participants were living in extended families. More than half (54.3%) of the participants were having 3-4 children and 51.4% of the participants were illiterate. A total of 112 codes were extracted. Overall five these were extracted from 20 categories which highlighted the perception of mothers regarding malnutrition in children under five years old. These five extracted themes were “Lack of Awareness”, “Contributing Factors”, “Poor socioeconomic status”, “Poor quality of diet” and “Poor child Health”. Conclusions: Parents perceived that they done have enough understanding regarding malnutrition. Besides, poor hygiene, improper nutrition, lack of balance diet is some of the contributors of malnutrition among children under five years old. In order to improve parents’ knowledge of the appropriate feeding methods for infants and children, health promotion activities should be strengthened at child welfare clinics, health facilities, and at the community level